Factors for Joining Village Community Networks in Tanzania - Madaha, Rasel (International Journal of Social and Administrative Sciences, 2021)
Self-created social networks play key role in the development of communities across the globe. Self-created community networks serve as platforms for social networking among marginalized communities in Africa and the rest of the world. Although community members are motivated to network, social networks face some micro and macro structural challenges. Despite the challenges, community members continue to join and benefit from social networks. However, the reasons for them to join the networks, especially in the African context, are inadequately documented. Using a qualitative methodology and longitudinal research design, the article explores “push and pull” factors for joining a strand of self-created social network known as Village Community Networks (VCONEs). The findings suggest that challenges emanating from the neoliberal context push some community members to join VCONEs. The push prompts them to seek some protection against the negative forces of neoliberalism. VCONEs also pull women to access opportunities offered by the network. Noteworthy, VCONEs have managed to retain some autonomy from external agents such as local governments, donor and NGOs. The autonomy from external agencies makes VCONEs more sustainable than other strands of social networks.